Beginning Level Interior Design Students’ Perceptions and Use of Research in Design Process - Dazkir, Sibel Seda (International journal for the scholarship of teaching and learning, 2019)
This study was focused on beginning-level interior design undergraduate students' perceptions, experience, and use of literary research. The data were collected through a questionnaire that was administered to 67 students. The findings indicated that the majority of the students searched for information in their classes, and the participants were aware of the importance of research. However, only 63% of them reported using credible sources in their literary research, and less than half of the respondents knew what a peer-reviewed journal article is. Based on the findings, it was suggested that students need to develop skills in conducting literary research using credible sources, and they need more exposure to research-inspired design and a wider range of topics that they could research in interior design. The findings could be used to develop new teaching strategies and to improve assignment handouts related to research-inspired design in interior design education.